1995
DOI: 10.1136/pgmj.71.834.244
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-induced pericarditis and pericardial effusion; first reported case

Abstract: SummaryWe report a case of methotrexateinduced pericarditis and pericardial effusion in a 22-year-old pregnant woman. These complications have not previously been described as isolated phenomena associated with methotrexate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 3 publications
0
14
0
2
Order By: Relevance
“…Two of these patients had shortness of breath associated with pleuritic chest pain. One woman developed a pericardial effusion (Forbat et al, 1995). In total, 49 women (19.6%) experienced grade I/II vaginal bleeding during the first course and 38 women (15.2%) during further courses.…”
Section: Toxicitymentioning
confidence: 99%
“…Two of these patients had shortness of breath associated with pleuritic chest pain. One woman developed a pericardial effusion (Forbat et al, 1995). In total, 49 women (19.6%) experienced grade I/II vaginal bleeding during the first course and 38 women (15.2%) during further courses.…”
Section: Toxicitymentioning
confidence: 99%
“…Anthracyclines, [75][76][77][78] The occurrence of pericardial and endomyocardial fibrosis years after administration of busulfan has also been described. 101 Other agents associated with pericardial disease are methotrexate, [102][103][104][105] arsenic trioxide, 106,107 and less frequently, 5-fluorouracil 108 and docetaxel. 109 Transthoracic echocardiography is the method of choice for the initial evaluation of patients with suspected pericardial disease.…”
Section: E Pericardial Diseasementioning
confidence: 99%
“…Methotrexate administration over 8 days may damage dividing mucosal or serosal cells with some selectivity for different sites. Forbat et al (1995) suggested that a cellular immune response might cause MTX-induced pericarditis based on the findings of Case 4, although the authors indicated that the possibility of an unrecognized viral infection or a reaction to an unsuspected allergen could not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray changes, if present, are non-specific -the most common abnormality being reticulonodular shadowing, usually diffuse and symmetrical with basal predominance. Pulmonary function tests may reveal reduced gas transfer and a restrictive ventilatory defect (Forbat et al, 1995). The differential diagnosis in these patients includes pneumonia, tumour lysis in those with pulmonary metastases and pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%